1982
DOI: 10.4315/0362-028x-45.10.964
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical and Biological Degradation of Mycotoxins in Foods and Agricultural Commodities

Abstract: Aflatoxin is partially or completely degraded by irradiation, heat, or treatment with strong acids or bases, oxidizing agents or bisulfite. Hydrogen peroxide plus riboflavin denature aflatoxin in milk. Mycelia of Aspergillus parasiticus can degrade aflatoxin, possibly via fungal peroxidase. Such degradation is affected by strain of A. parasiticus, amount of mycelium, temperature, pH and concentration of aflatoxin. Adsorbants, including bentonite and activated charcoal, can physically remove aflatoxin and patul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
14

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 0 publications
1
84
0
14
Order By: Relevance
“…Besides that, aflatoxins can be eliminated by the addition of bisulfate, strong acids, strong bases or oxidizing agent or treatment with strong acids or bases, oxidizing agents or bisulfite. Hydrogen peroxide plus riboflavin denature aflatoxin in milk (77). Chemical stability of Nivalenol, Deoxynivalenol and Zearalenone related to moisture, ph and heat was studied by Lauren and Smith (78) and the results showed that Nivalenol and deoxynivalenol are stable in buffer solutions that have the range of Ph 1-10, but with a Ph higher than 12, high salt concentration and a temperature of 80˚C for a long period of time, both Nivalenol and deoxynivalenol tend to break down.…”
Section: The Chemical and Physical Nature Of Mycotoxinsmentioning
confidence: 99%
“…Besides that, aflatoxins can be eliminated by the addition of bisulfate, strong acids, strong bases or oxidizing agent or treatment with strong acids or bases, oxidizing agents or bisulfite. Hydrogen peroxide plus riboflavin denature aflatoxin in milk (77). Chemical stability of Nivalenol, Deoxynivalenol and Zearalenone related to moisture, ph and heat was studied by Lauren and Smith (78) and the results showed that Nivalenol and deoxynivalenol are stable in buffer solutions that have the range of Ph 1-10, but with a Ph higher than 12, high salt concentration and a temperature of 80˚C for a long period of time, both Nivalenol and deoxynivalenol tend to break down.…”
Section: The Chemical and Physical Nature Of Mycotoxinsmentioning
confidence: 99%
“…Such actions are not always completely effective. Several possibilities are available as for the detoxification of mycotoxins, including physical and chemical methods [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…parasiticus were only able to achieve measurable degradation of aflatoxins when mycelium had been blended or fragmented. This may indicate that uptake of exogenous aflatoxins is strain-dependent (Doyle et al, 1982). The inhibitory effect of cycloheximide on the degradative effect confirmed the enzymic nature of the activity.…”
Section: Discussionmentioning
confidence: 51%